Characteristics of Atopic Dermatitis Patients who Underwent Skin Prick Test - Nugroho, Wisnu Triadi; Ervianti, Evy; Zulkarnain, Iskandar; Hidayati, Afif Nurul; Damayanti, Damayanti; Utomo, Budi; Cita Rosita Sigit Prakoeswa (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2022)
Background: Skin prick test (SPT) is indicated in type I hypersensitivity reactions (rapid type), among which is Atopic Dermatitis (AD). However, the results of SPT for the tested allergens are not always accompanied by history of known allergens in AD patients. Purpose: To identify the characteristics of AD patients who underwent SPT. Methods: This was a descriptive retrospective study to determine the demographics, allergy history, SPT results, and positive and negative clinical relevance in AD patients treated at Allergy Immunology Division of Dermatology and Venerology Outpatient Clinic Dr. Soetomo General Academic Hospital Surabaya-Indonesia from January 2017 to December 2019. Results: A total of 284 AD patients were included. The adult age group (20-59 years) predominated the AD patient's visit every year with 58 patients (60.42%), 47 patients (46.08%), and 65 patients (75.58%) in 2017, 2018, and 2019, respectively. Only 60 AD patients underwent SPT, where most patients were allergic to dust with 30 patients (50.0%). House dust mite (HDM) allergen had the highest percentage of positive SPT result with 41 patients (63.3%). The greatest clinical relevance was found in cat fur allergen, where all patients (100.0%) had clinical relevance to their SPT result. Conclusion: This study shows that most AD patients were in adult age group and had a history of dust allergy. The highest percentage of positive SPT result was found in HDM allergen and the greatest clinical relevance was found in cat fur allergen.